The Alte Donau: Successful Restoration and Sustainable Management An Ecosystem Case Study of a Shallow Urban Lake (Aquatic Ecology Series ;, 2018)
Here we report on a 25-year long-term sequence of measures to return a deteriorated recreational urban lake, Alte Donau in Vienna to acceptable water quality. Metropolitan waters require focused ecosystem management plans and intensive in-lake efforts. We explored physico-chemical conditions, food web from viruses to fish and water birds, the sediments, the littoral zone and the catchment, management and urban planning, and global warming. Several restoration techniques were tested and critically evaluated. The final management plan was based on bi-stable theory. During the recovery phase, numerous surplus adjustments had to be implemented to secure sustainable achievement.